2019
DOI: 10.3389/fonc.2019.01221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Putative Prognostic and Predictive Markers in Neuroblastomas: High Expression of PBX1 Is Associated With a Poor Response to Induction Therapy

Abstract: The survival rate for patients with high-risk neuroblastomas remains poor despite new improvements in available therapeutic modalities. A detailed understanding of the mechanisms underlying clinical responses to multimodal treatment is one of the important aspects that may provide precision in the prediction of a patient's clinical outcome. Our study was designed as a detailed comparative analysis of five selected proteins (DDX39A, HMGA1, HOXC9, NF1, and PBX1) in one cohort of patients using the same methodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Segmental chromosomal aberrations like 1p deletion, 11q deletion and gain of 17q are associated with clinically aggressive disease. IHC expression of some selected proteins, PBX1 and NF1 have been shown to be useful as predictive factors following chemotherapy 18 . Cellblock provides material to perform these ancillary tests.…”
Section: Discussionmentioning
confidence: 99%
“…Segmental chromosomal aberrations like 1p deletion, 11q deletion and gain of 17q are associated with clinically aggressive disease. IHC expression of some selected proteins, PBX1 and NF1 have been shown to be useful as predictive factors following chemotherapy 18 . Cellblock provides material to perform these ancillary tests.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual developmental defects; CAKUTHED (Mary et al, 2022) Endometrial Carcinoma: Tumor suppressor (Guo et al, 2023) Ovarian Cancer: Oncogene (Park et al, 2008), chemoresistance (Jung et al, 2016) Prostate Cancer: Proliferation (Kikugawa et al, 2006;Liu et al, 2019b) Renal Clear Cell Carcinoma: Cell proliferation via JAK2/STAT3 signaling (Wei et al, 2018) Bladder Cancer: Cell growth, invasion, EMT (Zhao et al, 2022) Gastrointestinal system/ digestive tract Gut aplasia in Pbx1 −/− mice (Selleri et al, 2001) Gastric Carcinoma: potential oncogene (upregulation of miR650 and EMT) (Liu et al, 2021); potential tumor suppressor (upregulation of its PBXIP1 inhibitor) (He et al, 2017) Colorectal Cancer: Metastasis inhibition (Dai et al, 2023) Mouse model of hepatocellular carcinoma: tumor suppressor (upregulation of its PBXIP1 inhibitor) (Xu et al, 2013) Pancreas and pancreatic islands development (Kim et al, 2002) Diabetes mellitus (suggested) (Kim et al, 2002) Lung Lungs development (Li et al, 2014) Non-Small Cell Lung Cancer: Proliferation promotion (Lin et al, 2022) or tumor suppression (Sun et al, 2023) Lymphangioleiomyomatosis: cell survival by inducing expression of antiapoptotic genes (Olatoke et al, 2023) Lung hypoplasia (Mary et al, 2022) Brain Differentiation of olfactory bulb, mesencephalic and midbrain dopaminergic neurons (Sgadò et al, 2012;Remesal et al, 2020); hindbrain segmentation through control of RA synthesis (Vitobello et al, 2011) Brain cancer. Neuroblastoma: higher expression levels in the initial tumor samples compared with responders (Veselska et al, 2019); Glioma: tumor suppressor role) (van Vuurden et al, 2014) Parkinson: reduced levels in dopaminergic neurons (Villaescusa et al, 2016) Other ectoderm derivatives Epithelial cells: Corneal morphogenesis (Murphy et al, 2010); modulation of body-site-specific epidermal barrier (seen with Pbx1 epidermal-specific null mice), auditory sensory epithelium (Li et al, 2020b) Oral squamous cell carcinoma: Oncogene…”
Section: Hematopoietic Systemmentioning
confidence: 99%